Evaluating Chromosomal Microdeletions And Duplications: Ethical Considerations In Life Expectancy For Pediatric Bilateral Cryptorchidism – A Local Community Perspective - Wissam Saleh Hakim; Mohammed Aboud; Manal Kadhim (International Journal of Health and Pharmaceutical (IJHP), 2025)
Introduction & Objectives: Cryptorchidism is one of the most frequent congenital birth defects in male children and is present in 2–4% of full-term male births. The study aims to validate the associated genomic information to pick up and catalog life expectations with our community's associated syndromes and pathologies. Materials & Methods: The study was carried out between the 1st of June 2014 and the end of December 2018. G-banding of metaphase chromosomes and high-resolution karyotype analysis was performed in all patients using 5 DNA probes, ordered in the deletion intervals, and correlated with the cytogenetic map of the chromosome and sequence tagged size (STS) in the molecular study of microdeletion and microduplication using fluorescence in situ hybridization (FISH). The data were translated to the Statistical Package for Social Science (SPSS) version 22, Excel 2016 . Results: Out of 124 managed and operated on patients, genitourinary anomalies were the most common associated pathologies in 44% of cases, and hypospadias was the most common in 21.77%. Developmental delay and intellectual disabilities with speech disorders are considered the second one 24.19%. Y chromosome microdeletions were observed in 75% of all, the most considered one Y q1.2 D in 45.16%, p-value < 0.05. X p11.2 micro duplications were observed in 8.78% of the cases. Higher ascent of the testis presented with more microdeletion (intra-abdominal 35.48% of the patients) p-value < 0.05.  With the STS, sY84 & sy86, and the loci, DYS 273 & 148 the azoospermia factor A region (AZFa) was estimated in 39.51% of the patients. Conclusions: Genomic information and screening are recommended for bilateral   cryptorchidism as the chromosomal microdeletions and microduplications have been associated with a spectrum of pathologies, considering this with a catalog of the multidisciplinary team and complete disease network to follow up the clinical pictures after surgery.